ОСОБЛИВОСТІ ВИКОНАННЯ ЦИРКУЛЬНИХ СПРЯЖЕНЬ (Педагогіка вищої та середньої школи, 2009)
In the article, we consider the closure between the parameters of circular conjugations and how to use it in the educational process of the university.